Non-Surgical Strategies for Managing Skeletal Deformities in a Child with X-Linked Hereditary Hypophosphatemic Ricket: Insights and Perspectives - Tung-Hee Tie; Wei-Han Lin; Ming-Tung Huang; Po-Ting Wu; Meng-Che Tsai; Yen-Yin Chou; Chih-Kai Hong; Chii-Jeng Lin; Chien-An Shih (MDPI AG, 2024)
This case report sheds light on the management of skeletal deformity in a young child with X-linked hypophosphatemia (XLH), emphasizing the significance of a timely orthotic intervention alongside pharmacological treatment, which is a strategy not frequently highlighted in the XLH literature. The patient, a 2-year-and-7-month-old female, presented with classic XLH symptoms, including short stature, pronounced genu varum, and hypophosphatemia, with deformities observed in both the coronal and sagittal planes of the femur and tibia. Despite initial reliance on pharmacotherapy, which proved insufficient for skeletal realignment, the integration of orthotic treatment at age 3 marked a pivotal turn in the management strategy. By the age of 5 years and 9 months, this combined approach yielded significant improvements: the deformities in the femur and tibia were notably corrected, tibial torsion was addressed, and enhanced limb alignment was achieved, as corroborated by radiographic evidence. This case underscores the effectiveness of orthotic intervention as a critical and underemphasized adjunct to pharmacological therapy in managing XLH in early childhood. It advocates for the early inclusion of orthotic measures to optimize treatment outcomes and expand the range of management strategies for limb deformities.